Size-differential photosynthetic traits of phytoplankton in the Chukchi Sea. (15th February 2023) - Lee, Sang H.; Yun, Mi Sun; Jang, Hyo Keun; Kang, Jae Joong; Kim, Kwanwoo; Lee, Dabin; Jo, Naeun; Park, Sang Hoon; Lee, Jang Han; Ahn, So Hyun; Stockwell, Dean A.; Whitledge, Terry E.
Abstract: Understanding size-differential productivity characteristics of phytoplankton is important to evaluating climate-driven environmental changes in marine ecosystems. In this study, we derived the relative contribution of small phytoplankton (Psmall ; <5 μm) to the total primary production (TPP) and characterized their photosynthetic traits in comparison to large phytoplankton (Plarge ) based on field-measured observations in the Chukchi Sea, 2012. The overall chlorophyll- a (51.8 ± 23.1%) and TPP contributions (52.3 ± 29.8%) of Psmall observed in this study were closely related to freshwater contents. In regards to nitrogen uptake, Psmall contributed 39.0% (S.D. = ± 28.4%) and 73.4% (S.D. = ± 50.1%) to the total nitrate uptake rate (TNP) and the total ammonium uptake rate (TAP), respectively, which is consistent with previous findings. Particulate and assimilated carbon/nitrogen (C/N) ratios were significantly ( p  < 0.01 and 0.05, respectively) lower in Psmall compared to Plarge, indicating their different natural capacities during growths. A significantly negative relationship was observed between the Psmall contribution and the TPP in the Chukchi Sea. These results imply that the more Psmall contribution in marine ecosystems could lead the less C sequestration from euphotic depths to deep ocean. In comparison to other regions, a more rapid decreasing TPP in the Chukchi Sea with increasing Psmall contribution is distinctively noticeable, which suggest that the Chukchi Sea ecosystem could be more vulnerable to an expected increase in Psmall contribution. Highlights: Contribution of small phytoplankton is closely related to freshwater content in the Chukchi Sea. Significantly lower C/N ratios of small phytoplankton in comparison to large phytoplankton. Strong negative relationship between small phytoplankton contribution and the total primary production. Chukchi Sea ecosystem could be more vulnerable to increasing small phytoplankton.